Female Pattern Hair Loss in Female and Male: A Quantitative Trichoscopic Analysis in Chinese Han Patients - Chen, Xi (Front Med (Lausanne), 2021)
Objectives: To investigate the trichoscopic features of female pattern hair loss (FPHL) in Chinese Han patients and analyze the difference between male and female patients with FPHL. Materials and Methods: Trichoscopic images were taken in four different scalp areas, including right frontal hairline, vertex, right parietal and occipital areas. Hair density, hair shaft diameter, vellus hair ratio and single hair follicle unit ratio were counted manually and analyzed. Results: Seventy-three subjects were enrolled in this study, including 38 patients with FPHL (28 females and 10 males) and 35 normal controls without hair loss. The hair density and hair shaft diameter of FPHL patients reduced in the whole scalp. Vellus hair ratio and single hair follicle unit ratio were both increased in FPHL compared to normal controls. The vertex was the most affected area and the hair shaft diameter showed the most significant difference. Parietal and occipital area were also affected in FPHL. The reduction or increase was correlated with the severity of Ludwig staging. Very few gender differences were detected in male and female FPHL patients. Conclusion: FPHL patients showed decreased hair density and hair shaft diameter, accompanied by increased vellus hair ratio and single hair follicle unit ratio. Parietal and occipital area can be also affected in FPHL, though not as severe as in vertex area. FPHL in male basically has the same characteristic as those in female patients. Limitation: The main limitation of the study is the small sample size which only enrolled 10 male FPHL patients, in comparison to the female cases. The findings could not be representative of the normal population with the limited sample size.